The Solutions of Partial Differential Equations with Variable Coefficient by Sumudu Transform Method - Bulut, Hasan; Baskonus, H. Mehmet; Tuluce, Seyma (Amer Inst Physics, 2012)
In this paper, we studied to obtain numerical solutions of partial differential equations with variable coefficient by Sumudu Transform Method (STM). We applied to three examples this method. Then, we ploted 2D and 3D graphics of these equations by means of programming language Mathematica. In order to solve these differential equations which is ordinary and partial, the integral transforms such as the Laplace, Hankel and Fourier were unusually used and therefore there are several works on literature and applications of them. But it has few been given by using STM. And thus, in recent years STM has been an important places in applied sciences such as especially engineering, physics, physical sciences. Moreover, it is important for solving ordinary and partial differential equations which is linear and nonlinear.
9th International Conference on Mathematical Problems in Engineering, Aerospace and Sciences -- JUL 10-14, 2012 -- Tech Univ Vienna, Vienna, AUSTRIA
Keywords: Sumudu Transform Method; Partial Differential equations with variable coefficient